EVALUATION OF MEDIA COMPONENTS AND REPLACE THEM WITH SEA WATER FOR SCYTONEMIN PRODUCTION BY USING NOSTOCALES - PRANAY ABHANG; GIRISH PATHADE (International Journal of Pharma and Bio Sciences, 2015)
Scytonemin is a naturally occurring UV screening pigment, found in extracellular sheaths of most of the Nostocales. Accumulation of scytonemin in extracellular sheath is regulated by many of the nutrients and physiochemical parameters. The purpose of this study was to evaluate BG 11 media component by using Plackett-Burman statistical design and study their effective concentrations on the production of scytonemin, by using four isolated Nostocales Scytonema sp., Plectonema sp., Spirulina sp., and Lyngbya sp. All four fresh water cyanobacteria were adopted for 3% salinity and BG 11 media is then replaced with sea water, by adjusting evaluated components and providing optimum physiochemical conditions for scytonemin production. As per our results, NaNO3 (nitrate), K2HPO4 (phosphate + potassium), CaCl2 (calcium) and MgSO4 (Magnesium) has a significant effect on scytonemin production. NaNO3 concentration varies from 0% to 0.015%. MgSO4 at 10 times more concentration increases scytonemin yield by 2 folds. CaCl2 presence decreases scytonemin yield, optimized concentration was 10 time less as that of original concentration. Optimized concentrations for pH, salinity and temperature were 7- 8, 2% and 28 – 30 0C, respectively. Scytonemin produced by using sea water culture was about 2.5% of dry weight of all 4 cyanobacteria.